Transformative Physical Rehabilitation : Thriving After a Major Health Event - Dubouloz Wilner, Claire-Jehanne, 1951- (Book collections on Project MUSE., 2020)
"In adult physical rehabilitation, the transformative learning theory offers a detailed model of Meaning Perspective Transformation in Physical Rehabilitation based on research evidence, with examples and cases, and presents guidance for clinical applications. This book draws from the theoretical background of transformative learning in adult education (Mezirow) to discuss the expansion and transfer of knowledge to clinical rehabilitation and community health rehabilitation settings for rehabilitation interventions. It also presents innovative findings of a fifteen-year research project on the process of meaning perspective transformation with client/patient groups. This project generated the first model of transformative change in the field of physical rehabilitation, built on successive, externally funded research projects that were completed for the first time with any of these client populations undergoing interventions in occupational therapy, physiotherapy, and other physical health rehabilitation disciplines. The book is written for clinicians, educators, and students of physical rehabilitation, as well as for those who are interested in helping a loved one deal with personal change."--